ECO-PSYCHOLOGICAL ANALYSIS OF BIMBOâ€™S BELALANG SONG LYRIC: A DISCOURSE PERSPECTIVE - Nurhamidah, Idha; Purwanto, Sugeng; Rustipa, Katharina (International Journal of Humanity Studies (IJHS), 2020)
The current study investigated Bimboâ€™s Song lyric entitled â€˜Belalangâ€™ in a Discourse Perspective. It has come to be known that Bimbo is a senior music group, specializing in deep philosophical touches of romantic songs. Belalang is a song attempting to create an analog of an insect (mantis) with special mating behaviors to human love affairs tied in dangerous wedlock. The lyric was analyzed in two ways, (1) to find out the field, tenor and mode of the discourse, employing the analytical framework of Systemic Functional Linguistics (SFL) in a macro sense, and (2) to find out the eco-psychological phenomena, employing the analytical framework of eco-psychology. The findings show that both mantis (with its special mating behavior) and humansÂ Â  (in showing true love to the â€œdestructiveâ€ wife) have a similar patternâ€”to preserve the ecosystem or in other words to create a conducive environment. The moral teaching seems to support the old saying that to love does not necessarily own despite the presence of love-chemistry. A seemingly peaceful marital life has to come to its end due to an unexpected mystical curse of Bahu Laweyan.Â  Yet, secondary love can be made possible in search of peaceful lives, to avoid self-destruction.